(untitled) (African Human Mobility Review, 2021)
West Africa is known across the world for its admirable adherence to its longheld principles of hospitality and inclusion. It is also a sub-region whose population shares a deep common history, a fact that is ever more evident in the on-going integration of the politics and communities of this highly mobile area. States in the region have advanced measures for disaster risk management and response, and are forward looking in terms of the implications of climate change. Many relocation projects have already been developed and implemented in some West African countries, generally within national borders, in response to environmental disasters (e.g. contamination of the Niger River) or for economic reasons (e.g. villages relocated in western Ghana to make way for mining companies). Although fewer examples exist, some relocation projects specifically concern persons vulnerable to the adverse effects of climate change.